EFEKTIVITAS MODEL PROJECT-BASED LEARNING TERHADAP KETERAMPILAN MENULIS AKADEMIK MAHASISWA KELAS 1 BK UNUGIRI - Tawakkal, M. Iqbal; Djoko Apriono; Sumadi (Universitas Islam Malang, 2025)
Abstract: This research is motivated by the low academic writing skills of students caused by learning that is still theory-oriented and does not involve direct experience. The purpose of this study is to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving the academic writing skills of first-year students of Guidance and Counseling (BK) UNUGIRI. The research method uses a quantitative approach with a pretest-posttest control group design. The research subjects consisted of 60 students who were divided into experimental and control groups. Data were collected through academic writing tests and analyzed using the t-test. The results showed that there was a significant difference between the experimental and control groups, where students who studied with the PjBL model showed a higher increase in academic writing skills. Thus, the PjBL model is effectively applied in academic writing learning in higher education.